China between Empires The Northern and Southern Dynasties - Lewis, Mark Edward 1954- (Harvard University Press, 2021)
After the collapse of the Han dynasty in the third century CE, China divided along a north-south line. This book traces the changes that both underlay and resulted from this split in a period that saw the geographic redefinition of China, more engagement with the outside world, significant changes to family life, developments in the literary and social arenas, and the introduction of new religions
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: HISTORY / Asia / China